Late Onset Psychosis with Affective Symptoms: Clinical Nuances or a Diagnostic Conundrum? - Mittal, Ruchi; Rijal, Rika; Sharma, Babita; Gupta, Anoop Krishna (Med Phoenix, 2024)
Introduction: In schizophrenia prodrome, when symptoms frequently resemble those of depressive illnesses, it creates a diagnostic challenge for clinicians, especially if it is late onset. This also has treatment implications in old age. Case presentation: A 65-year-old female who presented with mood and psychotic symptoms pose diagnostic dilemma. Careful history, collateral examination and continual exploration were done for accurate diagnosis and proper management. Due to overlapping symptoms, the initial diagnosis of psychotic depression was revised to paranoid schizophrenia. Eventually, the detailed examination, neurological and laboratory work up were done and the treatment approach was adjusted. The diagnostic dilemma appeared during the initial stage of the late onset psychosis due to affective symptoms. This case emphasises the critical role of clinical acumen in identifying the possibility of schizophrenia and other psychoses, ruling out organic aetiology and balancing the need of psychotropic drugs in old age.